Donjuán i Pan Niedziela - Jan Kordys (Przestrzenie Teorii)
The essay provides an interpretation of a scene (dialogue Don luan - Monsieur Dimanche; IV, 2) from Molière's Dom luan ou le Festin de pierre in several complementing discursive orders. The first relates to the formal theory of cooperation (R. Axelrod, W. Hamilton), the second - to Marcel Mauss's essay, The Cift: Forms and Functions of Exchange in Archaic Societies, and the subsequent - to the typology of speech acts and subject's attitudes towards the order of signs. Models, created on this basis, serve as tools for the analysis of the relations between Don Juan, other people, God, and of his attitude to love, gift, obligations and death. The protagonist violates communication rules ordering society and its institutions. The destruction of the most important rule, the rule of reciprocity, shows simultaneously the cognitive mechanisms conditioning exchange, use of performatives, understanding of the sign as a tripartite structure of signifiersignified-designation.